2023
DOI: 10.1038/s41598-023-29655-0
|View full text |Cite
|
Sign up to set email alerts
|

Greater traditionalism predicts COVID-19 precautionary behaviors across 27 societies

Abstract: People vary both in their embrace of their society’s traditions, and in their perception of hazards as salient and necessitating a response. Over evolutionary time, traditions have offered avenues for addressing hazards, plausibly resulting in linkages between orientations toward tradition and orientations toward danger. Emerging research documents connections between traditionalism and threat responsivity, including pathogen-avoidance motivations. Additionally, because hazard-mitigating behaviors can conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…In prior work using the same sample as the current study (Samore et al, 2023), we found that greater traditionalism tended to correlate with taking more public health precautions. This finding is consistent with the hypothesis that greater sensitivity to threats-including pathogen threats-is associated with greater traditionalism, given that practicing the tried-and-true may have threat-mitigating benefits.…”
Section: Does Traditionalism Associate More Strongly With Religious V...supporting
confidence: 51%
See 4 more Smart Citations
“…In prior work using the same sample as the current study (Samore et al, 2023), we found that greater traditionalism tended to correlate with taking more public health precautions. This finding is consistent with the hypothesis that greater sensitivity to threats-including pathogen threats-is associated with greater traditionalism, given that practicing the tried-and-true may have threat-mitigating benefits.…”
Section: Does Traditionalism Associate More Strongly With Religious V...supporting
confidence: 51%
“…The cultural environment is likely to shape the perception of conflicts between religion and science, in part as a function of dynamics such as information environments (e.g., rhetoric from faith or scientific leaders, or from news media or political figures), the particularities of different faith traditions, and historical path dependencies. These same dynamics apply to the COVID-19 pandemic, where individuals' perceptions of the costs, benefits, and tradeoffs of various precautions varied widely (Samore et al, 2023), likely structuring cross-culturally variant perceptions of conflict or compatibility between religious and public health precautions.…”
Section: Do Religious and Public Health Covid-19 Precautions Correlat...mentioning
confidence: 94%
See 3 more Smart Citations